Systematic Literature Review: Penerapan dan Dampak Integrasi Kearifan Lokal dalam Pembelajaran Bahasa Arab-Indonesia di Madrasah Ibtidaiyah - Nurjannah, Siti; Wisudawati, Asih Widi (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
This review aims to systematically examine existing literature to identify the implementation and impact of local wisdom integration in Arabic-Indonesian language learning at Madrasah Ibtidaiyah. This approach has the potential to enrich the learning experience by incorporating cultural values and local traditions that can strengthen students' character. The method used is a Systematic Literature Review (SLR), with data collected through searches in electronic databases such as Scopus, ScienceDirect, ResearchGate, Google Scholar, and Semantic Scholar using relevant keywords. This review includes literature published between 2020 and 2024, with inclusion criteria focusing on empirical studies, the integration of local wisdom, and the context of Arabic-Indonesian language learning. The findings indicate that integrating local wisdom can enhance students' language comprehension and proficiency. A local wisdom-based approach not only connects learning with cultural values but also supports character development through contextual and relevant education. Despite challenges such as low student motivation and limited teacher competence, the review findings suggest that innovative learning models incorporating local wisdom can overcome these obstacles. Therefore, curriculum development that integrates local wisdom values, along with improvements in facilities and environmental support, is essential for creating an effective and meaningful learning experience.